Loss of Sustained Activity in the Ventromedial Prefrontal Cortex in Response to Repeated Stress in Individuals with Early-Life Emotional Abuse: Implications for Depression Vulnerability - Wang, Lihong; Paul, Natalie; Stanton, Steven J.; Greeson, Jeffrey M.; Smoski, Moria (Frontiers in Psychology, 2013)
Repeated psychosocial stress in early life has significant impact on both behavior and neural function which, together, increase vulnerability to depression. However, neural mechanisms related to repeated stress remain unclear. We hypothesize that early-life stress may result in a reduced capacity for cognitive control in response to a repeated stressor, particularly in individuals who developed maladaptive emotional processing strategies, namely trait rumination. Individuals who encountered early-life stress but have adaptive emotional processing, namely trait mindfulness, may demonstrate an opposite pattern. Using a mental arithmetic task to induce mild stress and a mindful breathing task to induce a mindful state, we tested this hypothesis by examining blood perfusion changes over time in healthy young men. We found that subjects with early-life stress, particularly emotional abuse, failed to sustain neural activation in the orbitofrontal and ventromedial prefrontal cortex (vmPFC) over time. Given that the vmPFC is known to regulate amygdala activity during emotional processing, we subsequently compared the perfusion in the vmPFC and the amygdala in depression-vulnerable (having early life stress and high in rumination) and resilient (having early life stress and high in mindfulness) subjects. We found that depression-vulnerable subjects had increased amygdala perfusion and reduced vmPFC perfusion during the later runs than that during the earlier stressful task runs. In contrast, depression resilient individuals showed the reverse pattern. Our results indicate that the vmPFC of depression-vulnerable subjects may have a limited capacity to inhibit amygdala activation to repeated stress over time, whereas the vmPFC in resilient individuals may adapt to stress quickly. This pilot study warrants future investigation to clarify the stress-related neural activity pattern dynamically to identify depression vulnerability at an individual level.